2015
DOI: 10.1017/jfm.2015.517
|View full text |Cite
|
Sign up to set email alerts
|

Water–substrate physico-chemistry in wetting dynamics

Abstract: We consider the wetting of water droplets on substrates with different chemical composition and molecular spacing, but with an identical equilibrium contact angle. A combined approach of large-scale molecular dynamics simulations and a continuum phase field model allows us to identify and quantify the influence of the microscopic physics at the contact line on the macroscopic droplet dynamics. We show that the substrate physico-chemistry, in particular hydrogen bonding, can significantly alter the flow. Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…These simple atoms are non-charged and do not form hydrogen bonds with water molecules. See [12] for further details. The initial radius R of the water droplets are 50 nm and their width w = 4.67 nm.…”
Section: Appendix: Simulation Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…These simple atoms are non-charged and do not form hydrogen bonds with water molecules. See [12] for further details. The initial radius R of the water droplets are 50 nm and their width w = 4.67 nm.…”
Section: Appendix: Simulation Set-upmentioning
confidence: 99%
“…A recent study has shown that the no-slip condition in dynamic wetting is a consequence of liquid molecules forming hydrogen bonds with substrate molecules [12]. Hydrogen bonds are a particular class of transient and non-covalent electrostatic bonds between polar molecules, such as water.…”
Section: Introductionmentioning
confidence: 99%
“…From the applied mathematical point of view, Navier slip regularisation leads to an approximation in which the curvature still diverges logarithmically at the contact line and to a contradiction if the velocity field is continuous [20,21]. Moreover certain fluid and surface combinations have very small slip lengths, below the nanometer scale [22,23]. In such systems, if one considers the problem at smaller and smaller scales, other molecular effects will become relevant before the slippage effects.…”
mentioning
confidence: 99%
“…Temperature (v-rescale) and pressure (Parrinello-Rahman) were controlled by using weak coupling thermostats [15,16]. Electrostatic interactions were treated by means of Particle Mesh Ewald (PME) approach [17,18]. Initial atomic velocities were created on the basis of Maxwellian distribution at the absolute temperature [19,20].…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%